Analysis and improving countermeasures of medical disputes from the perspective of legal changes - Zhang Linlin; Zhang Shimeng (Journal of Otology)
Under the background of medical disputes growing in number, scale and intensity, tracing back legal changes in medical field as a breakthrough point, this paper took a legal perspective to illustrate changes in medical dispute settlements from legislative orientation to legal system improvement. In view of the fact that early legislation in medical field was biased towards identification and punishment of doctors’ responsibility, and later intensive legislation in balancing increasing ''medical trouble'' phenomenon with limited effects and difficulties to abide by the law, this paper proposed to improve doctor-patient dispute settlements system in China referencing from foreign law experience, to reduce investigation of doctors at the judicial level, and to establish a settlement mechanism on doctors' apology at the legislative level, so as to promote a healthy development of doctor-patient relationship.